Migration and the Constant Search for Self-Improvement in Africa - Kandilige, Leander; Ampah, Geraldine Asiwome; Abutima, Theophilus Kwabena (African Human Mobility Review, 2024)
Globally, narratives about the nexus between migration and development have gained prominence among academics, policymakers, development practitioners, as well as social partners. However, the historical and contextual factors that have shaped the patterns of migration flows within and from the African continent have been poorly conceptualized and theorized. The components of migration that have the propensity to lead to self-improvement and development such as the sending of cash, social, and political remittances; skills and knowledge transfers; and diaspora-origin country engagements, need to be examined as a composite in order to fully appreciate the developmental potential of migration within the African context. Using thematic and content analysis of relevant extant literature, we examine the contextual factors that characterize the nexus between migration and self-improvement/development in Africa. Our analyses are situated within an Africa-centered conceptualization of development and migration. We argue that the development impacts of migration vary across different regions in Africa depending on the contextual factors that shape such migrations. Migration spurs self-improvement and development just as self-improvement and development facilitate migration.